Crystallization of polymers in variable external conditions. 1. General equations - Ziabicki, A.
A new model of crystallization kinetics in variable external conditions has been developed. The model concerns situations when temperature, pressure, stress, change in time. Compared to earlier models, the present treatment includes transient and athermal effects, proportional to the rate of change of the external conditions. The model can be used for simulation of crystallization in industrial processes (injection molding, fiber spinning, film blowing). The present paper offers general theoretical fundamentals of the model. Applications concerning more specific cases will be published separately.
Keywords: CRYSTALLIZATION; NUCLEATION; GROWTH - NON-ISOTHERMAL CRYSTALLIZATION; THERMAL NUCLEATION; ATHERMAL NUCLEATION; TRANSIENT EFFECTS; RELAXATION TIMES